Factors Associated with the Implementation of Medical Records at the Konawe District Health Center, Indonesia - sitti marya ulva; Nurleni Nurleni; La Ode Saafi; Sunarsih Sunarsih; Erwin Azizi Jayadipraja; La Ode Bahtiar (Public Health of Indonesia)
Background:The implementation of medical records is vital to ensuring quality healthcare services by supporting patient care, administrative functions, and policy development. However, challenges such as limited resources, inadequate training, and insufficient infrastructure often hinder optimal medical record practices in health centers, particularly in developing regions like Konawe District, Indonesia.